Comparison of the effect of patient-centred and family-centred education through smartphones on the quality of life of patients with type 2 diabetes: A quasi-experimental study - Danial Mohammadi-Avizi; Mohammadreza Firouzkouhi; Abdolghani Abdollahimohammad; Mahin Naderifar (PAGEPress Publications, 2024)
Diabetes is one of the most common non-communicable metabolic diseases with debilitating complications that affect the quality of life of patients. Therefore, the present study aimed to determine the effect of patient-centred and family-centred education via smartphone on the quality of life of type 2 diabetic patients. This is a quasi-experimental study with a three-group design (patient-centred education, family-centred education and patient-family-centred education) that was conducted on patients with type 2 diabetes and their families in 2022. Research subjects were selected by the purposive sampling method. The collected data were analyzed using SPSS ver. 21. The results showed no significant difference between the three groups in terms of age, sex, marital status, educational level and duration of diabetes. There was a significant difference between the three groups in terms of the mean total quality of life (QoL) score before and after the intervention (p <0.05). In other words, in addition to having a better score than the previous intervention in the three groups after the intervention, the total QoL score was better in the patient-family-centred education group. The results of the present study showed that patient-family-centred education has a greater impact on QoL scores. Therefore, healthcare providers and policymakers should pay more attention to this issue.